2016
DOI: 10.1002/mop.29807
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-integrated waveguide diplexers with improved Y-junctions

Abstract: Y‐junctions are often adopted to design diplexers since their characteristics can conveniently satisfy the constraints for optimum performance of diplexer design. In order to decrease the size of the Y‐junction diplexer, the two branches of the junction can be bent to yield parallel outputs. However, this parallel configuration can degrade the characteristic of the Y‐junction. In this letter, two improved novel configurations of Y‐junction diplexers are introduced, analyzed with an efficient mode‐matching base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Different ways to obtain bismuth nanostructures have been reported. On one hand, the obtaining of BiNPs can be performed form bulk metallic bismuth by using thermal decomposition; however, this method usually is not efficient enough in terms of production yield [14]. On the other hand reductive methods to synthesize BiNPs also have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Different ways to obtain bismuth nanostructures have been reported. On one hand, the obtaining of BiNPs can be performed form bulk metallic bismuth by using thermal decomposition; however, this method usually is not efficient enough in terms of production yield [14]. On the other hand reductive methods to synthesize BiNPs also have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed that the electric field is restricted around the CSRR. [1][2][3][4][5][6][7][8] The comparison transmission responses by circuit model and full-wave simulation FIGURE 4 Dispersion diagram of HMSIW-CSRR FIGURE 5 The E-field distribution in the HMSIW loaded by CSRR (A) (B) FIGURE 6 The comparison between simulated and measured (A) input port (port 1) return loss (S 11 ) and isolation between filter channel ports (S 23 ); and (B) channel filter return losses (S 22 and S 33 ) FIGURE 7 The comparison between simulated and measured transmission loss (S 12 and S 13 )…”
Section: Csrr Hmsiw Filter Analysismentioning
confidence: 99%
“…Undoubtedly, diplexers are one of the most important sections in transceivers for millimeter and microwave multiband and service systems. [1][2][3][4][5][6][7] Diplexer proverbial as a three ports structure which two output ports are located at the end of two filters with different passband. In fact, three ports are employed to isolate transmit/receive signal linked a common antenna.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the evanescent-mode technique attracts an extreme attention because of easy etching some components on the top or bottom metal surface of the SIW structure [7][8][9][10]. According to this theory, an additional forward passband at the frequency range below the waveguide cutoff could be achieved by loading the electric dipoles on the metal cover of the SIW structure.…”
Section: Realization Of the Siw-ocsrr Filtersmentioning
confidence: 99%
“…This component provides a high bandisolation between two different output ports to avoid interference between each other. In order to achieve a few desired specifications for a high-performance diplexer in terms of low insertion losses, strong channel rejection and high isolation, this device can be realized by different filter configurations [5][6][7][8][9][10]. The SIW structures are suitable to realize essential filter elements of the diplexers because of the advantage of these structures.…”
Section: Introductionmentioning
confidence: 99%